LEARNING AND MOTIVATION RELATIONSHIPS ATTENTION PARENTS AGAINST STUDENT LEARNING OUTCOMES GEOGRAPHY CLASS X SMAN 2 BAYANG PESISIR SELATAN DISTRICT ACADEMIC YEAR 2012/2013 - PUTRA, DIKOMAI; Drs. Edi Suarto, M.Pd, Drs. Edi Suarto, M.Pd; SE, M.Si, Nefilinda, (Pendidikan Geografi, 2014)
ABSTRACT   This research aims to determine the relationship between motivation to learn and the parents attention on learning outcomes Geography students of class X student of SMAN 2 BayangPesisir Selatan district year 2012/2013.This research is a descriptive correlational . The population in this study were all tenth grade students of SMAN 2 Bayang. Data from SMAN 2 Imagine then, the population in this study is as much 135 people. Samples were taken with a sampling technique with a proportion of 30% for each class so that the sample of respondents totaled 87 students.The results of the study found that : 1) There is a relationship between motivation and learning outcomes Geography students of class X student of SMAN 2 BayangPesisir Selatan district because tcount > t table (7,238 > 1,665), the strength of a strong relationship (r = 0,622) and a small amount of the contribution (38,77%), 2) there is a relationship between parental concern with the outcomes geography students of class X student of SMAN 2 BayangPesisir Selatan district because of t > t table (7,174 > 1,665), including a strong relationship strength ( r = 0.614 ) and small contributions made (37,7%), and 3 ) There is a significant relationship between student motivation and parental concern together with the outcomes geography students of class X student of SMAN 2 BayangPesisir Selatan district because of F > F table (41.567 > 2.751), the strength of the relationship between the two variables Geography category with strong learning outcomes (r = 0,705) and including sizeable contribution (49,7%).